Asesmen Awal Permasalahan Peserta Didik dan Peran Penting Bimbingan Konseling di SD - Martaningsih, Sri Tutur; Muyana, Siti; Putri, Ragil Dian Purnama; Kurniawan, Shopyan Jepri (Universitas Muhammadiyah Metro, 2025)
Curriculum changes have operational consequences for their implementation by teachers as the frontline implementers. Not all teachers have easy access to curriculum socialization information, resulting in low understanding and difficulty in implementing the expected learning. On the other hand, elementary school is a transitional stage from preschool to formal school, which raises problems when children are not ready. Guidance and counseling (BK) as a party that can help intervene if there is a problem, there are no special personnel assigned to elementary schools. Guidance and counseling in elementary schools must still be carried out by class teachers. The golden age is at an early age (PAUD level) and early elementary school classes, requiring stimulation so that the development of various aspects is optimal. Class teachers with various administrative tasks and teaching tasks for almost all subjects will have difficulty providing stimulation for individual student development. The characteristics of lower and upper grade elementary school students are different, requiring a relevant BK learning/service approach. Child development problems can be experienced by children at the elementary school age stage, both in learning, personal, social, and career problems. Permendikbud 111 of 2014 has mandated that there are BK teachers in elementary schools, but its implementation in the field has not yet been realized. This article presents a study of various problems in elementary school children, furthermore it is expected that appropriate alternative solutions can be provided. After knowing the various problems in the field and also from theoretical studies, teaching materials or service materials can be developed that are enjoyable for students, in accordance with the development stage, and help facilitate class teachers in providing optimal development stimulation to their students.